PEMENUHAN HAK PEKERJA DALAM PEMUTUSAN HUBUNGAN KERJA AKIBAT EFISIENSI PADA PERUSAHAAN YANG TERDAMPAK PANDEMI COVID-19 - Helmy Alkatiri, (2022)
The Covid-19 pandemic is a disease outbreak that has hit almost all corners of the world, its rapid spread is a factor why this virus quickly spreads throughout the world, including Indonesia. The consequences of Covid-19 have caused Indonesia to make policies to minimize the spread of Covid-19 by suppressing activities outside the home. As a result, many companies suffer losses due to the decline in income, with this incident the company laysoff workers to reduce company expenses. Many companies do layoffs for reasons of efficiency because they have suffered losses or prevent losses due to the Covid-19 pandemic. How to prove the company in doing layoffs for reasons of efficiency and what compensation is given to workers affected by layoffs. The research method used is empirical juridical research using empirical facts obtained from interviews with employees who have been laid off. Proof that if the company is forced to lay off workers for reasons of efficiency, it is proven by the company's balance sheet which has been proven by a public accountant that the company has suffered a loss, as well as the compensation provided in accordance with PP Number 35 of 2021 Article 40, namely severance pay, long service awards, and compensation for entitlements. Where the company must take other efficiency measures before taking layoffs and companies that layoff are obliged to provide compensation if they do not get criminal sanctions. Keywords : Termination of Employment, Efficiency, compensation